Designed for accumulation by dispossession: An analysis of Tanzania's Wildlife Management Areas through the case of Burunge. Issue 1 (21st January 2021) - Kicheleri, Rose P.; Mangewa, Lazaro J.; Nielsen, Martin R.; Kajembe, George C.; Treue, Thorsten
Abstract: Unfortunately, adverse rather than positive local welfare outcomes of community‐based conservation initiatives are quite common. Through the case of Burunge Wildlife Management Area (WMA) this study documents how WMAs in Tanzania appear designed to facilitate accumulation by dispossession in the name of decentralized wildlife management. Based on focus group discussions, interviews, and policy‐document analyses, we show that the process of establishing the WMA was fraught with hidden agendas and lacked legitimacy as well as transparency. Villagers and their local governments were also oblivious to the fact that the village land they contributed to forming the WMA would no longer be under village control even if they withdrew from the WMA. Decentralized revenue streams were gradually recentralized, and when the High Court ruled in favor of a Village Government that did not want to be part of the WMA, higher levels of government scared it to stay and to drop its legal as well as economic claims. We conclude that by mechanisms of rule‐through‐law WMAs deliberately dispossess village communities by attenuating the authority of democratically elected village governments. Hence, the wildlife policy needs urgent revision to democratize and thus promote positive livelihood outcomes of the WMA concept. Abstract : Through the case of Burunge Wildlife Management Area (WMA) in Tanzania, this study shows how the design of decentralization can facilitate accumulation by dispossession. We found that the process of establishing the WMA was fraught with hidden agendas and lacked legitimacy as well as transparency. Using rule‐through‐law, the central government gradually recentralized initially decentralized revenue streams and wrestled authority over village lands from democratically elected village governments, which were unaware that village land contributed to forming the WMA would no longer be under their control, even if they withdrew from the WMA. We conclude that WMAs appear designed for accumulation by dispossession and suggest an urgent revision of policy legislation to re‐establish the authority of democratically accountable village governments and level the playing field between them, international conservation organizations, and the central government.